Svenskämnet i skärmkulturen - Erixon, Per-Olof (Tidskrift för litteraturvetenskap, 2010)
School Subject Paradigms and Teaching Practices in the Screen Culture Like many other countries, Sweden has invested heavily in new technologies and new media in school. An advanced ICT use is assumed to lead to an educational change and improve teaching. But, the incorporation of ICT differs from subject to subject. Such aspects have so far been essentially neglected in research on ICT in a pedagogical discourse. School subjects have their own universal and characteristic structures, which may be of great importance for how ICT can be integrated. School subjects are in varying degrees and in different ways in accordance with ICT. This article takes it point of departure in the school subject Swedish, which is increasingly under the influence of a digital media and screen culture. The result shows that the subject paradigm is challenged by new technology, which could lead to a »paradigmatic« change. This article, which is based on a pilot study in a bug research project called »School subject paradigms and teaching practices in the screen culture«, puts the question of what this may entail for the (1) content and (2) teaching methods in the school subject Swedish. The results show that new technology destabilizes the subject paradigm and challenge the pedagogical discourse.